Role of hepatitis c virus in hepatocellular carcinoma and neurological disorders: an overview - Suhail, Mohd; Sohrab, Sayed Sartaj; Kamal, Mohammad Amjad; Azhar, Esam Ibraheem (Frontiers in Oncology, 2022)
Hepatitis C virus (HCV) causes serious issues affecting 71 million people globally. The most common manifestation ranges from chronic hepatitis to liver cirrhosis leading to hepatocellular carcinoma. This virus is also associated with impairment of the central nervous system resulting in acute or sub-acute encephalopathy and inflammatory disorders. Neurological disorders are associated with the inflammatory responses of many cells, including microglia and astrocytes. In addition, there are many other extrahepatic manifestations, including neurological disorders such as depression and fatigue, in 50% of infected patients. These manifestations include neuro-invasion, immune-mediated damage, neurotransmitter alterations, sensory-motor polyneuropathy, sensitivity loss, weakness of the leg, and cryoglobulinemia which significantly results in reduced life quality. The HCV infection may be improved by using the proper diagnosis, and direct antiviral therapy sustained virological response. However, the success of therapy depends on the symptoms and organ damage, diagnosis, and therapeutic strategies applied. This review aims to provide an overview of the latest information about the progress made for the diagnosis, physio-pathological mechanisms, and strong antiviral therapies developed for HCV infection, as well as the latest advancements made in the study of the neurological disorders associated with HCV infection.